Code Visualization for Performance Improvement of Java Code for Controlling Smart Traffic System in the Smart City - Bo Kyung Park; Geon-Hee Kang; Hyun Seung Son; Byungkook Jeon; R. Young Chul Kim (Applied Sciences, 2020)
In an intelligent smart city like Sejong city in Korea, automatic and smart software is absolutely necessary for autonomous traffic and vehicles control systems. Therefore, these systems need to have an accurate and timely performance; otherwise, safety issues may arise. To resolve this, we propose our code visualization approach to adapt an object-oriented smart traffic control simulator, which analyzes Java code’s complexity and identifies bad codes against performance. To achieve an accurate performance, we must repeatedly perform refactoring until attaining a range of system-defined performances through effective code visualization. As a result, we enhance the code complexity of the cyber-physical system-based software to achieve the exact performance. With this approach, we expect to obtain an accurate performance and complexity improvement of the object-oriented traffic control simulator without significant power consumption.